2019
DOI: 10.1080/13880209.2018.1557700
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-osteoarthritis effect of Mollugo pentaphylla extract

Abstract: Context: Mollugo pentaphylla L. (Molluginaceae) extract (MPE) has been reported to have anti-inflammatory effect on MSU-induced gouty arthritis in a mouse model. Objective: This study examined the anti-inflammatory activities of an MPE in vitro and anti-osteoarthritis effects on monosodium iodoacetate (MIA)-induced osteoarthritis (OA) in vivo. Materials and methods: The dried whole plants of M. pentaphylla were extracted with 70% ethanol under reflux. The anti-inflammatory effect of MPE was evaluated in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Pain assessment assay commonly used is the incapacitance test, which measures the weight distribution between both hind limbs [37]. e pain of knee joint leads to decrease of hindpaw weight-bearing distribution (HWBD), which has been proved in the previous study [34]. e HWBD on 0, 1, and 2 weeks is measured in Figure 1.…”
Section: Change In Hindpaw Weight-bearingmentioning
confidence: 82%
“…Pain assessment assay commonly used is the incapacitance test, which measures the weight distribution between both hind limbs [37]. e pain of knee joint leads to decrease of hindpaw weight-bearing distribution (HWBD), which has been proved in the previous study [34]. e HWBD on 0, 1, and 2 weeks is measured in Figure 1.…”
Section: Change In Hindpaw Weight-bearingmentioning
confidence: 82%
“…To date, there is no definite treatment for this chronic disease and most of the therapeutic methods are focused on symptom management and in severe cases, joint replacement is considered [4,5]. Previous experiments concluded that the prevention of anti-inflammatory and pro-inflammatory pathways as well as reducing oxidative stress may lead to controlling the development of the OA [6,7]. Numerous studies found that some herbal medicines due to their immune modulating, anti-inflammatory, and antioxidative effects can prevent OA in experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, HMOX1 also played an indirect role in the development of GA [22]. MMP2 and MMP9 were the members of the matrix metalloproteinase (MMP) family, which increased cartilage degradation, further resulting in the development of GA [23]. SERPINE1, one of the serine protease inhibitors, played a pathophysiological role in the synovial fluid of gouty arthritis [24].…”
Section: Ppi Networkmentioning
confidence: 99%